Gaya Penerjemahan “Funktionsvergfüge” Pada Novel Herr Der Diebe Karya Cornelia Funke - Uryadi Uryadi (Makassar State University, 2019)
The objective of this research is to analyze the translation of German “Funktionsverbgefüge” (verbal-nominal constructions) into bahasa and to find out the understanding of translating procedure, the equivalences and deviations in translating the forms. This research methodology is qualitative using content analysis technique. Data were sentences using the FVG. They were taken from a roman ‘Herr der Diebe” by Cornelia Funke and its version in bahasa. There were 137 FVG found and analyzed. The result of this research shows that (1) there are expressions using FVG were translated with five translating procedure, (2) it was found that the translated phrases habe communicative equivalences with the source sentences, and (3) the translating deviations found were most becouse of the translators failure in finding the right words.